Exploring the landscape of climate change education in China: trends, knowledge, attitudes and behaviours among university students and teachers - Zilin Qin; Lifu Jiang (International Journal of Climate Change Strategies and Management)
Purpose – This study aims to investigate climate change education (CCE), including global trends and specific implementations in China, as well as the worldwide development of CCE and its key components, including knowledge, attitudes and behavioural patterns. Design/methodology/approach – The authors combined bibliometric analyses and a targeted questionnaire based on the knowledge–attitude–practise (KAP) model to investigate CCE. Initial global trends identified through VOSviewer guided the study survey, focusing on Chinese university students and educators’ knowledge, attitudes and practices. Findings – The high level of concern about climate change among Chinese students and educators and their actual understanding of this issue often results in overconfident self-assessment. Academic specialisation significantly influences the level of climate change concern, with humanities and social sciences students and educators demonstrating higher concern than their counterparts in the natural sciences. The study highlights the essential role of effective climate policy dissemination in shaping informed attitudes and behaviours, particularly in a government-driven policy landscape like China’s. Climate policy awareness, positive emotions, self-efficacy, collective efficacy and personal experiences all positively impact Chinese youths’ climate change engagement. CCE is primarily delivered uniformly across China through policy instructions and specific courses, yet more engaging, interactive and localised educational approaches to CCE that are tailored to regional and cultural contexts are needed. Originality/value – Combining bibliometric analysis with survey data, this research uniquely highlights the significance of the political context in China, emphasising the critical role of policy dissemination in shaping climate change perceptions and actions, addressing regional differences and the local context. Based on the KAP model, the study proposed a new model for implementing CCE in collectivist societies like China.